Value relevance of book values and earnings of listed non-financial firms in South Africa: a dynamic panel analysis. (24th August 2019) - Sixpence, Atanas; Adeyeye, Olufemi Patrick
We analyse value relevance of book values and earnings before interest and taxes (EBIT) using a dynamic panel of non-financial firms listed on the Johannesburg Stock Exchange (JSE). In the aftermath of the global financial crisis, we seek to find out if share prices are linked to financial statement variables. A random sample of twenty-seven high- and low-capitalised firms was used. Using two-step System GMM with net asset value per share and average debt/equity ratio as additional regression instruments, we found EBIT to be value relevant but book value lacks value relevance. Analysts and investors on the JSE should thus focus more on EBIT when analysing companies they intend to invest in and should pay less attention to book value. Accounting standard setters can also put more measures that protect the integrity of reported EBIT as a way of helping investors and ensuring that accounting statements remain useful to investors.